2017
DOI: 10.1038/s41598-017-02863-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of optimal weight gain during pregnancy for Japanese Women

Abstract: This study aims to compare the US Institute of Medicine (IOM) and Japanese guidelines proposed by the Ministry and the Japan Society for the Study of Obesity on gestational weight gain (GWG), and to explore the optimal GWG range in Japanese women. We investigated 8,152 Japanese women who had full-term singleton babies between 2010 and 2013 at a single center in Tokyo. Logistic regression models showed that GWG below the recommendation of the IOM and Japanese guidelines was similarly associated with an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 13 publications
4
38
0
1
Order By: Relevance
“…The prevalence of eating disorders among Japanese women has been increasing over time (Nakai et al 2014), similarly to other countries (Kimmel et al 2016;O'Brien et al 2017). Eating disorders are common psychiatric disorders among women of reproductive age, and a variety of pregnancy-related complications have been reported (Rondo et al 2003;Koubaa et al 2005;Micali et al 2007Micali et al , 2012Micali et al , 2016Bulik et al 2009;Hoffman et al 2011;Linna et al 2014;Kimmel et al 2016;O'Brien et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of eating disorders among Japanese women has been increasing over time (Nakai et al 2014), similarly to other countries (Kimmel et al 2016;O'Brien et al 2017). Eating disorders are common psychiatric disorders among women of reproductive age, and a variety of pregnancy-related complications have been reported (Rondo et al 2003;Koubaa et al 2005;Micali et al 2007Micali et al , 2012Micali et al , 2016Bulik et al 2009;Hoffman et al 2011;Linna et al 2014;Kimmel et al 2016;O'Brien et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, to our knowledge, despite the increasing numbers of patients, no studies on maternal eating disorders in Japan have been reported in the English or Japanese literature. Because the incidence of eating disorders might be related to race, socioeconomic status, and cultural factors (O'Brien et al 2017;Nakai et al 2018), the clinical characteristics and perinatal outcomes of Japanese women with a history of eating disorders need to be clarified in order to decrease the risk of poor health in mothers and children.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-pregnancy weight and its gain during pregnancy are two factors which might significantly affect the course of pregnancy and neonatal health. Women who are too slim before conception are at a higher risk for delivering a low birth weight (LBW) or a small for gestational age (SGA) infant, while overweight or obese women are at risk for gestational diabetes, fetal macrosomia, or a large for gestational age (LGA) infant [13,14,18,26,34]. Inadequate and excess pregnancy weight gain may both have negative consequences but, in the era of global obesity, the research has visibly focused on the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Excess weight gain during pregnancy is associated with numerous complications, e.g. gestational diabetes, arterial hypertension [19,23,28], and fetal macrosomia [14,29,34]. Currently, it is believed that excess neonatal weight intensifies the problem of obesity both, in childhood and later in life [3-5, 10, 14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some large studies in Japan investigated optimal GWG; [3][4][5][6] however, they may have insufficiently assessed the influence of GWG on the incidence of preeclampsia because GWG with preeclampsia is often due not only to eating habits, but also increased edema associated with renal and/or vascular endothelial dysfunction. Edema that accompanies preeclampsia often leads to weight gain just before the onset of preeclampsia, unlike that due to eating habits.…”
Section: Introductionmentioning
confidence: 99%